2018
DOI: 10.1016/j.invent.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the development and dissemination of internet cognitive behavioral therapy (iCBT) for anxiety disorders in children and young people: A consensus statement with recommendations from the #iCBTLorentz Workshop Group

Abstract: Initial internet-based cognitive behavioral therapy (iCBT) programs for anxiety disorders in children and young people (CYP) have been developed and evaluated, however these have not yet been widely adopted in routine practice. The lack of guidance and formalized approaches to the development and dissemination of iCBT has arguably contributed to the difficulty in developing iCBT that is scalable and sustainable beyond academic evaluation and that can ultimately be adopted by healthcare providers. This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 76 publications
0
47
0
Order By: Relevance
“…Despite its limitations, the findings of this study are encouraging and certainly justify further research in an RCT or similar design to confirm the effectiveness of this type of intervention. Historically, there has been a lack of formalized approaches to the dissemination of iCBT interventions [ 14 ], yet there are some recent design recommendations that may be appropriate. To address the challenges of conducting controlled trials in real-world implementation settings, it may be necessary to conduct a stepped-wedge cluster design, which is increasingly recommended for evaluation of service delivery interventions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its limitations, the findings of this study are encouraging and certainly justify further research in an RCT or similar design to confirm the effectiveness of this type of intervention. Historically, there has been a lack of formalized approaches to the dissemination of iCBT interventions [ 14 ], yet there are some recent design recommendations that may be appropriate. To address the challenges of conducting controlled trials in real-world implementation settings, it may be necessary to conduct a stepped-wedge cluster design, which is increasingly recommended for evaluation of service delivery interventions [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been relatively little research examining the implementation of iCBT programs for child and adolescent anxiety in real-world clinical and community contexts (eg, outside university-based research trials); furthermore, there are no formalized guidelines for a large-scale dissemination [ 14 ]. One small feasibility study has very recently been reported by Jolstedt et al [ 15 ], where an evidence-based iCBT program for anxiety was implemented in a small sample (N=20) of anxious children in an outpatient clinic in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…After the end of the workshop, the paper has been finalized by means of an open online document combined with email conversations and Skype meetings. The trustworthiness and credibility of such a collaborative approach to the analysis of data and scientific writing has earlier been applied by some of the participating researchers (Hill et al 2018;Jandrić 2019;Jandrić et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Service user involvement has been encouraged in Government policy for over 15 years (Department of Health andSocial Care, 2005, 2006; European Group on Ethics in Science and New Technologies, 2015) but is rarely achieved or well described, especially at the initial stages of trials (Briel et al, 2016;O'Cathain, Thomas, Drabble, Rudolph, & Hewison, 2013). One of the key challenges is how to support service users' participation in the research process in a truly meaningful way (Hill et al, 2018).…”
Section: Introductionmentioning
confidence: 99%